PENERAPAN PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEAKTIFAN DAN KEMAMPUAN SISWA DALAM MEMAHAMI KONSEP HUBUNGAN MANUSIA DENGAN KONDISI GEOGRAFIS DI SEKITARNYA PADA KELAS IV SDN KETINTANG I/409 SURABAYA - Sari, Dewi Kartika; Kasdi, Aminuddin; Warsono, Warsono (Universitas Negeri Surabaya, 2020)
ABSTRACTThe purpose of this study is to describe the students? activity and skill achivement to comprehend the lesson material (student activement) in applying the inquiry learning model in IPS subject, concept comprehending the human in their relationship with the geographical condition around them, on the fourth grade of SDN Ketintang I/409 Surabaya. The design of this research is classroom action reasearch with three cycles of activities. The objects are 35 fourth grade students of SDN Ketintang I/409 Surabaya. The data is obtained from the observation and test result. The observations is conducted to observe the student?s activities during the learning process, while the test is performed to measure the students? ability in comprehending the material (students? studing achievement). Based on the data analysis result, it can be concluded that after applying the inquiry learning model, the student? activities and studying achivement were improved. if in the cycles I the activity percentage is only 61,28% and the studying achivement is 63%, then in cycle II the activity percentage became 73,2%and the studing achievement became 74,3%, and in cycle III the activity percentage reached up to 82,9% and the studying achievement reached up to 85,71%. These activity and studying achievements were caused by the learning process wich involved the student to find out the material concept by themselves.Keywords: Comprehending Skill, Inquiry Learning Model, Students? Activity.ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui peningkatan keaktifan siswa, dan kemampuan siswa memahami materi pelajaran (hasil belajar) dalam penerapan model pembelajaran inkuiri pada mata pelajaran IPS konsep hubungan manusia dengan kondisi geografis di sekitarnya kelas IV SDN Ketintang I/409 Surabaya. Desain penelitian ini adalah penelitian tindakan kelas dengan 3 siklus kegiatan. Objek penelitian yaitu 35 siswa kelas IV SDN Ketintang I/409 Surabaya. Data diperoleh dari hasil observasi dan tes. Observasi dilakukan untuk mengamati keaktifan siswa selama proses pembelajaran, sementara tes dilakukan untuk mengukur kemampuan siswa memahami materi (hasil belajar siswa). Berdasarkan hasil analisis data dapat disimpulkan bahwa setelah menerapkan model pembelajaran inkuiri, keaktifan dan hasil belajar siswa mengalami peningkatan. Jika pada tindakan siklus I persentase keaktifan mencapai 61,28% dan ketuntasan hasil belajar 63%, siklus II keaktifan 73,2% hasil belajar 74,3%, dan pada siklus III keaktifan mencapai 82,9% dan hasil belajar mencapai 85,71%. Peningkatan keaktifan dan hasil belajar ini disebabkan oleh proses pembelajaran yang melibatkan siswa untuk menemukan sendiri konsep materi yang dipelajari.Kata Kunci: Keaktifan Siswa, Kemampuan Memahami, Model Pembelajaran Inkuiri.